Adoption value of serum hematological inflammatory markers in early diagnosis of necrotising enterocolitis - Luo Ruogu; Zhang Jing; Li Xiaolong; Peng Fei; Zhang Anpeng; Zhang Pengfei (Journal of Medical Biochemistry)
Background: Early diagnosis and intervention of neonatal necrotising enterocolitis (NEC) are crucial for improving prognosis. It was to assess the diagnostic and staging value of high-sensitivity C-reactive protein (hs-CRP), white blood cell count (WBC), and interleukin (IL)-6 levels in NEC, and to explore their correlation with disease severity. Methods: This retrospective study analysed clinical data from 43 NEC patients in the neonatology department of Northwest Women and Children's Hospital, designated as the experimental group (EG), and concurrently selected 38 healthy newborns as the control group (CG). Serum hsCRP, WBC, and IL-6 were measured in both groups. Statistical analyses were performed using SPSS 27.0. Results: hs-CRP, WBC, and IL-6 in NEC patients greatly surpassed those in healthy newborns, and these markers were notably positively correlated with NEC staging (r=0.756, 0.234, 0.901, P<0.05). Combined detection of hs-CRP, WBC, and IL-6 in early NEC diagnosis yielded an AUC of 0.988, with a sensitivity of 93.02% and specificity of 97.37%, all superior to individual detections (P<0.05). Conclusions: hs-CRP, WBC, and IL-6 are essential in diagnosing and assessing NEC, particularly combined detection, which greatly improves early diagnostic accuracy. Future research should further investigate additional inflammatory markers to optimise diagnostic methods, providing a more comprehensive scientific basis for early clinical intervention and treatment.